2015
DOI: 10.1159/000440819
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Double-Stranded RNA Poly(I:C) Aggravates IgA Nephropathy by Triggering IgA Class Switching Recombination through the TLR3-BAFF Axis

Abstract: Background: Immunoglobulin class-switch recombination (CSR) is crucial for the expression of IgA, and it plays a vital role in the physiopathology of IgA nephropathy (IgAN). The aim of the study is to investigate the effect of polyriboinosinic:polyribocytidylic acid (poly(I:C)) in modulating toll-like receptor (TLR) 3-B-cell-activating factor belonging to the TNF family (BAFF) axis activation, which in turn promotes IgA CSR of IgAN patients and the IgAN rat model. Methods: Blood samples and tonsillar tissue sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…The method inducted a successful rat model of IgAN based on our previous studies [24]. In brief, rats were induced with continuous oral immunization containing 0.1% bovine gamma globulin (BGG) (Sigma) with 6 m M HCl in tap water for 18 weeks, followed by tail intravenous injection of 1 mg BGG daily for 3 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method inducted a successful rat model of IgAN based on our previous studies [24]. In brief, rats were induced with continuous oral immunization containing 0.1% bovine gamma globulin (BGG) (Sigma) with 6 m M HCl in tap water for 18 weeks, followed by tail intravenous injection of 1 mg BGG daily for 3 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…All the renal staining was performed on 4-μm paraffin sections as we previously described [24]. In brief, immunohistochemical stains were performed on formalin-fixed, paraffin-embedded 4-μm sections.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, TLR1 (CT and CC genotype in rs4833095, TT genotype in rs5743557) (23) and TLR10 genes (TA and AA genotype in rs1004195) (24) may be associated with susceptibility to IgAN in Korean children. Recently, He et al (25) reported that the TLR3-B-cell activating factor axis was involved in IgA class switch recombination in IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…The group of He L. et al [103] offered more direct evidence of the involvement of dsRNA in IgAN. In this paper, human leukocytes, isolated from tonsil tissue and whole blood, were cultured with or without poly(I:C) for 1-7 days.…”
Section: The Interplay Between the Microbiome And Virome: A New Visiomentioning
confidence: 99%
“…The TLR3 crosstalk with BAFF plays a vital role in the over-production of IgA and in the Recombinant Class Switch to IgA in IgAN. Thus, the inhibition of TLR3/BAFF axis activation could be an interesting option for preventing IgAN progression [103].…”
Section: The Interplay Between the Microbiome And Virome: A New Visiomentioning
confidence: 99%